The differential relationship between self-control and peer influences over time: toward an integrative model of offending using a dual-systems approach - Yim, Ha-Neul (Crime & delinquency, 2021)
The purpose of this study is to explore an alternative approach to unravel how both self-control and peer influence relate to offending. Deriving from a dual-systems framework, this study hypothesizes that individuals with varying levels of self-control will be differentially susceptible to the effects of both exposure to deviant peers and informal socializing with peers. Analyses are based on a sample of serious youthful offenders from the Pathways to Desistance Study. The results indicate that exposure to deviant peers has a stronger impact on offending for individuals with higher self-control, consistent with the hypothesis. However, individuals with higher self-control are more vulnerable to unstructured and unsupervised socializing with peers than those lower in self-control, which counters the hypothesis.